Diseño e implementación de un modelo de gestión de inventarios en la empresa Importaciones Gómez Hermanos (2015)
It identifies the company IMPORTACIONES GOMEZ HERMANOS in running their inventories has struggled in its operational and administrative processes, for this reason it is proposed design and implement a model of inventory management where manuals, forms, flow charts, indicators are made management that contribute to the technical development of each process to be performed by officials who have direct contact with inventories and so is not affected economic growth of the company. This is a company dedicated to the purchase, sale and distribution of spare parts for motorcycles across the country, the behavior of this market in Colombia is very competitive, which requires a lot of organization with respect to inventories because management is needed that is suitable for handling these. The core of this work is the area of inventories, which is why seven people were chosen because these are directly responsible for the operation of this area